2005 IEEE Engineering in Medicine and Biology 27th Annual Conference 2005
DOI: 10.1109/iembs.2005.1617020
|View full text |Cite
|
Sign up to set email alerts
|

A Method of Recognizing Finger Motion Using Wavelet Transform of Surface EMG Signal

Abstract: In this paper, an identification method of finger motions using the wavelet transform of multi-channel electromyography (EMG) signal is presented. The first step of this method is to analyze surface EMG signal detected from the subject's upper arm using the multi-resolution of wavelet transform, and extract features using the variance, maximum and mean absolute value of the wavelet coefficients. In this way, a new feature space is established by wavelet coefficients. The second step is to import the feature va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 6 publications
0
30
0
Order By: Relevance
“…Different sEMG-based systems were proposed for the estimation of hand and wrist movements, and consequently used as noninvasive interfaces for controlling exoskeletons [5,6], prosthetic devices [7][8][9], computer-animated hands in a virtual environment [10], or for teleoperating robotic arms [9,11]. The previous studies focused on the investigation of discrete classifications of wrist abduction/adduction [9,11], flexion/extension [7,10,12,13] as well as of a different combination of finger motions [9,11,14]. Such strategies are useful for accomplishing power grasps that require simultaneous closure of all fingers on the object.…”
Section: Introductionmentioning
confidence: 99%
“…Different sEMG-based systems were proposed for the estimation of hand and wrist movements, and consequently used as noninvasive interfaces for controlling exoskeletons [5,6], prosthetic devices [7][8][9], computer-animated hands in a virtual environment [10], or for teleoperating robotic arms [9,11]. The previous studies focused on the investigation of discrete classifications of wrist abduction/adduction [9,11], flexion/extension [7,10,12,13] as well as of a different combination of finger motions [9,11,14]. Such strategies are useful for accomplishing power grasps that require simultaneous closure of all fingers on the object.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen, the number of electrode is greater than or equal to the number of classes in nearly all of these studies. Also, almost all of the current works only deals with small number of classes (less than 10) [11,[17][18][19][20]23,29,30]. Only an extremely small number of studies have reported classification results for more than 10 classes but they require large number of electrodes [21,[31][32][33].…”
Section: Related Workmentioning
confidence: 99%
“…Over the past decades, different electrode placement strategies have been investigated. Some researchers study the use of multichannel electrode arrays [20] or high-density EMG (large number of electrodes) strategy [21,22], while others explore the precise anatomical positioning approach [18,23].…”
Section: Related Workmentioning
confidence: 99%
“…The two frequency-domain features were median frequency and mean power frequency [16][17][18]. The twelve time-and frequency-domain features included maximum, singular value, average energy, VAR, standard deviation, and WL of wavelet coefficients and wavelet packet coefficients [19][20][21][22][23][24][25][26]. The three nonlinear dynamic features were entropy of wavelet coefficients, entropy of wavelet packet coefficients, and maximum of Lyapunov exponent [27][28][29].…”
Section: Feature Set Computation and Reductionmentioning
confidence: 99%